Assessment of physical-economic and environmental factors affecting urban Space vulnerability analysis in earthquake Enjoying passive defense( Case study: Area5 shahre rey,district 20 tehran ) - Masumeh Mohebati; Alireza estelaji (تحقیقات کاربردی علوم جغرافیایی)
Reducing the vulnerability of urban users in order to reduce the amount of damages using non-factor defense approaches that can be effective in creating a safe environment in cities. The most important goals is today's planners and urban managers are planning to implement it in cities. The aim of this study was to investigate the safety of urban spaces against earthquakes due to the principles of non-factor defense and identification of safety mitigation factors in District 5 of Shahre Ray. The research method is descriptive-analytic to explain the current situation and the response to research questions. Data collection method was based on the field of Venice Library (questionnaire) and analysis of data obtained using frequency test and factor analysis. Then, the fundamental variables of influence were analyzed by Pir-son correlation test for the effect or rejection of assumptions. Finally, the findings show that what is considered as the basis for the work must determine the different stages of an earthquake planning process in Tehran and It is a shahre ray that must be used when preparing any comprehensive or detailed plan and case. The results of the study showed that physical, economic and environmental factors (can influence the reduction of urban space Vulnerability (in area 5 Shahre Ray). At the end, offers and guidelines for the preventive observance of the principles of non-operating defense in Shahre Ray has been presented.